Inspired by Aditya Sharma

Calculus Level 4

In which step did we first make a mistake?

0 = i = 0 0 ( 1 ) = i = 0 ( 1 1 ) ( 2 ) = i = 0 1 i = 0 1 ( 3 ) = ( 1 + i = 1 1 ) j = 0 1 ( 4 ) = 1 + j = 0 1 j = 0 1 ( 5 ) = 1 + j = 0 ( 1 1 ) ( 6 ) = 1 ( 7 ) \begin{array} { l l l } 0 & = \displaystyle \sum_{i=0}^\infty 0 & (1) \\ & = \displaystyle \sum_{ i=0}^ \infty (1 -1) & (2) \\ & =\displaystyle \sum_{ i=0}^ \infty 1 - \displaystyle \sum_{i=0}^\infty 1 & (3) \\ & = \left ( 1 + \displaystyle \sum_{ {\color{#D61F06}i=1}}^ \infty 1\right) - \displaystyle \sum_{j=0}^\infty 1 & (4) \\ & = 1 +\displaystyle \sum_{ j=0}^ \infty 1 - \displaystyle \sum_{j=0}^\infty 1 & (5) \\ & = 1 +\displaystyle \sum_{ j=0}^ \infty (1 - 1) & (6) \\ & = 1 & (7) \\ \end{array}


Inspiration .

Step 1 Step 2 Step 3 Step 4 Step 5 Step 6 Step 7 No mistake

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Calvin Lin Staff
Oct 27, 2016

Step 3 is NOT ok, because we are not allowed to split the sum into 2 partial sums without further justification. It leads to issues like this. In particular, we are claiming that 0 = 0 = \infty - \infty , which is not true because the RHS is actually undefined.

Step 6 is NOT ok, because we are not allowed to combine the sum into 2 partial sums without further justification. In particular, we are claiming that = 0 \infty - \infty = 0 . (Of course, since we want the first step, it is step 3.)

The errors result in:

0 = ( 3 ) = 1 + = ( 6 ) 1 0 \stackrel{(3)}{=} \infty - \infty = 1 + \infty - \infty \stackrel{(6)}{=} 1

Every other step is correct. Here are some explanations:
Step 1 - The countable sum of 0's is 0. Recall that i = 0 \sum_{i=0}^\infty is actually lim n i = 0 n \lim_{n\rightarrow \infty} \sum_{i=0}^n , and this finite sum is 0, so the limit is also 0.
Step 4 - We can isolate the first term of a summation. There is no reordering of terms.
Step 5 - We can relabel the indices via j = i 1 j=i-1 and then j = i j=i in the other summation.


Note: What we are doing is taking the sequence ( a 1 b 1 ) + ( a 2 b 2 ) + (a_1 - b_1) + (a_2 - b_2 ) + \ldots and reodering the terms massively into the form

a 1 + a 2 + a 3 + b 1 b 2 b 3 a_1 + a_2 + a_3 + \ldots - b_1 - b_2 - b_3 - \ldots

In particular, the b 1 b_1 term is moved behind infinitely many a i a_i terms. In order to justify such an arbitrary rearrangement of terms, we must ensure that the sequences are absolutely convergent . This constitutes the "proper justification" that is required.

Of course, depending on the sequence, various other "proper justification" is allowed.

Sir doesn't the first step too lead to (zero) multiplied by infinity,which itself is indeterminate,isnt that erroneous??

Chirag Shyamsundar - 4 years, 7 months ago

Log in to reply

The countable sum of 0's is indeed 0.

While your statement is true, it doesn't reflect the current scenario. I've edited the solution to reflect why we are not in a case of 0 × 0 \times \infty .

Calvin Lin Staff - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...